Towards an ICT Integrated Management of School Curriculum: A Review of the Status in Secondary Schools in Uasin-Gishu and Nandi Counties- Kenya - Kimosop, Maurice Kibet; Mulwa, David Musyoki (Journal of Educational Policy and Entrepreneurial Research (JEPER), 2016)
This paper delves into the status of integration of ICTs in the management of the teaching learning process in secondary schools in two counties of Uasin Gishu and Nandi in Kenya. The main objective of the study was to examine the nature of ICTs in the schools, the capacity of users, and the level of integration of ICTs. The study employed the descriptive survey design. A total of 342 educators comprising of 57 head teachers and 285 teachers from 63 secondary schools at various stages of ICT integration were selected. Purposive sampling was used to select the head teachers and schools with functional ICTs while the teachers were selected using stratified random sampling. Data was collected through a questionnaire and an interview schedule. Data was analyzed descriptively by use of SPSS programme version 17 for frequencies, means and percentages. The results indicated that there was an acute shortage of computers but the few available were easily accessible to users. There was a high level of utilization of ICTs for the purpose of management of exams whereas integration into curriculum delivery and decision making was low. Most respondents were only trained on basic introductory computer programmes but few had been trained on application programmes for teaching and management. The study recommended that acquisition of computers be enhanced and the training of ICT to focus more on specialized application skills rather than basic operational skills. Head teachers should source for ICTs that enhance the performance of curriculum management practices. It is hoped that the study will benefit education policy makers and head teachers in adopting effective ICT integration strategies in secondary schools
Keywords: ICT Integration; Management of curriculum; ICT Resources; ICTs